The Failed Promise of Regulatory Variables - Harold J. Krent (Washington University Law Quarterly, 1995)
The concept of a regulatory variable is misleading. All statutory language is susceptible to numerous interpretations that would be impossible to predict in advance. And myriad changes in financial or social situations may make legislative directives difficult to apply in future generations.
Keywords: Law -- Interpretation & construction; Judicial review of administrative acts; Judicial discretion